Revitalisation Strategies of the Azerbaijani Wine Industry in the Post-Pandemic Period: Market Constraints, Government Policy and Pricing Strategy — Evidence from AZGRANATA - Lazgiyev, Yusif (My University, 2026)
This study, in addition to examining certain structural changes in pricing strategies and external market constraints in the Azerbaijani viticulture and winemaking sector in the post- pandemic period, also takes the activities of AZGRANATA LLC as the main object of its empirical analysis. One of the main analytical directions of the study is to assess the disruptive effects of the COVID-19 pandemic on both global and local trade networks, to identify significant changes in consumer behavior patterns, as well as to analyze the evolution of sales channel systems. At the same time, the study assessed the direct impact of state regulatory policies on the daily activities of local enterprises and long-term market competitiveness. The study used mixed methods, i.e. mixed mesos research based on the principle of parallel triangulation. Within this approach, quantitative survey indicators and qualitative thematic data were systematically recorded. It was appropriate to contribute both theoretically and research- wise when studying through the synthesis of both empirical data streams. Thus, the dissertation provides a reliable and data-based scientific basis for formulating public policy and implementing institutional reforms when determining optimized strategic pricing models for commercial wine producers.
Keywords: Azerbaijan; AZGRANATA; Wine Industry; Post-Pandemic Period; Market Constraints; Firm Performance; Government Policy; Pricing Strategy